(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study investigates the moderating role of tax justice on the relationship between tax education and revenue generation in Bayelsa State. While tax education has been widely recognised as a critical tool for enhancing tax compliance and boosting government revenue, its effectiveness is often influenced by taxpayers’ perceptions of fairness, transparency, and equity within the tax system. The study adopted a survey research design with a target population consisting of registered taxpayers (both individuals and business owners) and tax officials in Bayelsa State. A multistage sampling technique was employed, and the Cochran formula was used for sample size determination. A questionnaire was used as the primary source of data collection, with a total of 218 copies of questionnaires returned and used with descriptive, correlation matrix and multiple regression techniques for data analysis. The multiple regression analysis reveals that electronic tax education had a positive and significant relationship with revenue generation. Print tax education had a positive and significant relationship with revenue generation. Stakeholder tax education had a positive and significant relationship with revenue generation. Furthermore, tax justice positively and significantly moderates the relationship between tax education and revenue generation in Bayelsa State. The study concludes that tax education (electronic, print and stakeholder sensitisation) is a significant determinant of revenue generation, and tax justice significantly moderates the association between tax education and revenue generation in Bayelsa State. The study recommends, amongst others, that tax authorities should adopt a holistic approach by combining educational efforts with justice-enhancing reforms, and tax education initiatives should not only focus on technical aspects, but also address fairness, government accountability, and the rationale behind tax collection and revenue generation.